A clinical audit of the management of ADHD in children and adolescents and comparison between two treatment sites in Cape Town - Vrba, Kim (Department of Medicine, 2020)
Background: The diagnosis of Attention Deficit Hyperactivity Disorder (ADHD) at a prevalence rate of 5-8% has clear public health and service implications. Studies suggest that certain populations, especially those with lower socio-economic status, are not adequately identified and treated. Evidence-based guidelines aim to standardize practice, but implementing them in low-resource environments can be challenging. To assess compliance, clinical audits for ADHD management have been conducted in higher income countries, but, to our knowledge, there have been no such audits in sub-Saharan Africa. Here we performed a clinical audit of ADHD assessment and treatment and compared compliance between two clinic groups in Cape Town, South Africa. Objectives: The primary aim was to measure compliance in a South African context using the National Institute for Clinical Excellence (NICE) guidelines for ADHD as the gold standard. The secondary aim was to compare compliance and socio-demographics between a 'central’ group (attending a treatment site in an area associated with high socio-economic status) and a 'peripheral’ group (attending in areas associated with low socio-economic status) in Cape Town. Methods: A clinical audit was conducted (March-June 2013) on the case notes for 100 'active’ cases of children or adolescents diagnosed with ADHD. The 'central’ group consisted of patients attending the Red Cross War Memorial Children’s Hospital Neuropsychiatry Clinic. The 'peripheral’ group included cases from community clinics in Retreat, Vanguard, Heideveld, and Kensington. Fifty cases were randomly selected from each group. Data were captured using an audit template derived from NICE guidelines, and a socio-demographic template. Results: Overall, of the 17 audit standards tested none showed 100% compliance. Compliance with four standards was rated 'good’ (>80%): qualified diagnostician (86%), clinician contact with teacher (96%), side effect monitoring (84%), and offering Methylphenidate as first line treatment (80%). Compliance with five standards was 'fair’ (50- 79%): DSM-IV criteria documentation (60%), treatment plan including behavioral or psychological interventions (71%), attempted communication in the patient’s primary language (69%), documentation of the child’s perspective (76%), and monitoring treatment response on standard scales (71%). Compliance with eight standards was 'poor’ (< 0.0001); and treatment response monitoring using standard scales (80% vs. 62%, p = 0.047). Conclusions: Overall, compliance with NICE guidelines for ADHD was low. The central group performed better than the peripheral group in key areas, offering a greater array of treatment options and safer monitoring. We recommend the introduction of structured protocols with re-audit as a tool to improve the quality of service delivery and present an audit checklist to be used in future audit cycles.